Abstract Options - Plous, Phyllis; Colpitt, Frances; Mary and Leigh Block Art Gallery, Northwestern University, Evanston; Saisset Museum - University of Santa Clara, Santa Clara (Santa Barbara : University Art Museum, 1988)
Baumann-Hudson, Edith ; Dryer, Moira ; Glück, Heidi ; Haynes, Nancy ; Hayward, James ; Heilmann, Mary ; Lethbridge, Julian ; Miller, John M. ; Mogensen, Paul ; Westfall, Stephen
Abstract Options, University Art Museum, Santa Barbara, 6 January - 26 February 1989 ; Mary and Leigh Block Art Gallery, Northwestern University, Evanston, 4 April - 18 June 1989 ; de Saisset Museum - University of Santa Clara, Santa Clara, 9 July - 3 September 1989
boek